The Use of Puppet Stage Media in Learning Language Skills in Children of KB Darul - Witri Nur Afidah; Mukti Widayati; Benedictus Sudiyana (At Turots: Jurnal Pendidikan Islam, 2024)
The use of media in learning can help children provide meaningful experiences for students. The use of media in learning can make it easier for students to understand something abstract to become more concrete. Media has an important role in facilitating the learning process. This research aims to describe the planning, implementation and evaluation of the implementation of language skills learning using puppet stage media for Darul Falah KB children. This research uses a qualitative descriptive method with a focused case study strategy. This research data is the planning, implementation and evaluation of the implementation of language skills learning using puppet stage media for Darul Falah KB children. The sources of research data are informants, namely the Darul Falah Play Group teachers and 13 Darul Falah KB students, events/activities, namely the application of language skills learning using puppet stages at the Darul Falah KB, and documents. This research applies data collection techniques through observation, documentation and interviews. Researchers carried out data validity checking techniques using method triangulation and source triangulation. This research shows that the teacher carries out three learning steps which include planning, implementing and evaluating learning. The teacher makes a Learning Implementation Plan which includes the semester program, Weekly Learning Plan, and Daily Learning Plan. The planning tool must show (a) determination of themes and basic competencies and indicators as well as time allocation, (b) materials and activities developed, (c) methods used, (d) learning scenarios, (e) media used, and ( f) learning evaluation. The implementation of language skills learning using puppet stage media for KB Darul Falah children is analyzed from how the teacher prepares the lesson, the teacher's skills in opening the lesson, mastery of the material, the use of the storytelling method and its variations in learning, how the teacher provides various variations of stimulus, questioning skills, use of media, skills of closing the lesson. The activities carried out by the teacher include three stages of activities, namely preliminary activities, core activities and closing activities. Evaluation is carried out in 2 forms, namely to determine the development of children's language skills in learning from children's attitudes, speech and behavior through conversation and observation and to evaluate the process of using puppet stage media in learning language skills. The research results show (a) Teachers make learning plans in accordance with guidelines, student characteristics and school conditions; (b) Teachers can manage time allocation for the learning process; (c) The teacher uses a puppet stage with hand puppets according to the theme and content of the story, including accessories on the puppet stage; (d) The teacher motivates children to focus on activities by clapping, singing and chatting and telling stories in varied voices to attract attention; (e) When telling a story the teacher uses variations in voice according to the character, movements and facial expressions; (f) In the question and answer session and discussion after the storytelling activity the teacher uses language that is easy for children to understand; (8) The teacher carries out recalling of children to obtain developmental achievements in learning language skills using the puppet stage through question and answer and discussion methods; (9) The teacher's experience in adding puppet media to attract children's attention was added by using puppet stage media which was previously rarely used